UPAYA MENINGKATKAN KUALITAS PAPAN SEMEN LIMBAH INDUSTRI KAYU DENGAN PERLAKUAN BAHAN DAN KADAR PEREKAT - Sushardi, Sushardi (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2011)
Technology of cement board developed so chips industrial disposal of wood specially in the form of changeable lignoselulosa become material which is good for human prosperity. The waste upon which cement board will obtain double advantage this lessen the expense peculiarly and obtain substance with the higher economic value. The aim of the research is to know the influence of treatment of waste of particle and proportion of cement adhesive to nature of cement board which is made of by a industrial disposal wood. Factorial experiment arranged in a completely randomized design, with the test continue the Tukey. Factor used in this research is consisted of by the treatment of particle waste ( without treatment, cold soaking and hot soaking) and proportion of cement ( 150%, 200% and 250% from substance weight). Parameter measured were : water content, specific grafity, modulus of repture, modulus of elasticity and thick reduction effect of pressure 3 kg / cm 2 . Result of this research showed that waste of particle and proportion of cement gived very real influence to physical and mechanical properties of cement board. The physical and mechanical properties of cement board from industrial disposal, namely specific grafity, modulus of rapture and modulus of elasticity were suitable with DIN 1101 standard. Key Words : Cement board, industrial disposal, treatment of waste, proportion of cement